Grand Challenges Brazil: One decade of health research funding - Patricia de Campos Couto; Sarah Sampaio Py-Daniel; Gabriela Bardelini Tavares Melo; Marcos Takashi Obara; Antonia Angulo-Tuesta (Saúde em Debate)
ABSTRACT This study assessed the funding of research conducted using the Grand Challenges Brazil strategy, a collaboration between the Ministry of Health (MS) and the Bill & Melinda Gates Foundation (BMGF), to optimize efforts in seeking solutions to global health problems. A descriptive and retrospective approach was used, based on secondary data. The study analyzed resource distribution and funded research by year, region, institutions, and types of research. Between 2011 and 2020, 75 research projects were funded, with a total investment of PPP$ 48.61 million. Public and population health research, representing 40% of the total studies, received 55.51% of the investment (PPP$ 26.99 million). Most resources were allocated to public institutions, which received 85.33% of the funds, with a significant concentration in institutions from Southeastern Brazil. The ‘Eliminate Dengue: Brazil Challenge’ project stood out, absorbing nearly half of the total investments (PPP$ 21.95 million). These findings demonstrated that the strategy was significant in allocating resources to public health research. Future studies should explore how the knowledge produced is being used to inform and improve health policies, ensuring that research findings effectively translate into population benefits.